A hybrid multi-criteria decision making approach of ANP and TOPSIS to evaluate the optimum fuel blend in IC engine. (2015) - Sakthivel, G.; Ilangkumaran, M.
This paper describes an application of hybrid MCDM technique for the selection of optimum blend in fish oil biodiesel among the six alternative fuel blends diesel, B20, B40, B60, B80 and B100. Emission, combustion and performance parameters are considered as evaluation criteria. A single cylinder, constant speed and direct injection diesel engine with a rated output of 4.4 kW was used for exploratory analysis at different load conditions. The proposed model, analytical network process (ANP) is integrated with technique for order preference by similarity to ideal solution (TOPSIS) to evaluate the optimum blend. Here, ANP is used to determine the relative weights of the criteria, whereas TOPSIS is used for obtaining the final ranking of alternative blends. Alternative fuel blend evaluation in IC engine is a very important strategic decision involving decisions balancing within a number of criteria and opinions from the IC engine experts. The selection of an appropriate source of biodiesel and proper blending of biodiesel plays a major role in alternative energy production. This paper highlights a new insight into MCDM techniques to evaluate the best fuel blend for the decision makers such as engine manufacturers and R&D engineers to meet the fuel economy and emission norms.